2005
DOI: 10.3801/iafss.fss.8-753
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Modeling Of The Effect Of Fine Water Mist On The Small Scale Flame Spreading Over Solid Combustibles

Abstract: A CFD model has been developed to predict the behavior of the flame spread over solid fuels in water mist environment. A coupled analysis involving gas phase and solid fuel is considered using unsteady two-dimensional conservation equations describing the selfsustained flame propagation. Due to the analysis is focused on the mechanism of flame suppression at the flame leading edge, which is explicitly exposed to the mist, finite-rate chemical reaction is taken into account. The equations for water mist and vap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 14 publications
0
15
0
Order By: Relevance
“…We used the kinetics of thermal decomposition for deciduous and coniferous tree species [1,3,5,9] in numerical simulation. From the analysis [1,3,5,9] it can be concluded that forest materials of different regions differ in their thermophysical properties and kinetic parameters.…”
Section: Resultsmentioning
confidence: 99%
“…We used the kinetics of thermal decomposition for deciduous and coniferous tree species [1,3,5,9] in numerical simulation. From the analysis [1,3,5,9] it can be concluded that forest materials of different regions differ in their thermophysical properties and kinetic parameters.…”
Section: Resultsmentioning
confidence: 99%
“…Up to now, a large part of experimental and numerical works mainly focuses on relatively fundamental phenomena, using simplified test configurations, see for example Refs. [6,11].…”
Section: The Use Of Water Mist In Tunnelsmentioning
confidence: 99%
“…A few real-scale tunnel fire experiments have been conducted in the past, like the EUREKA program [11], the US Memorial Tunnel campaign [13], or the UPTUN project [9]. Such real-scale tests are very expensive because a large number of sensors are required to get a detailed measurement of velocity and temperature fields.…”
Section: The Use Of Water Mist In Tunnelsmentioning
confidence: 99%
“…As a result, water flow for fire fighting reaches significant values. Therefore, one of the main challenges of founders the modern fire extinguishing systems is increase the efficiency of water use [6].…”
Section: Introd Ctionmentioning
confidence: 99%
“…As a result, water flow for fire fighting reaches significant values. Therefore, one of the main challenges of founders the modern fire extinguishing systems is increase the efficiency of water use [6].The purpose of this work -the study of the evaporation of large single water droplets as it passes through the flames of oil and oil products with varying parameters of the processes (the initial size of 2-6 mm, the rate of 2-4 m / s and the temperature of the water droplets 290-300 K, the temperature of the combustion products 185-2073 K). …”
mentioning
confidence: 99%